Theories of choice : the social science and the law of decision making - Grundmann, Stefan, 1958-; Hacker, Philipp, 1985- (Oxford : Oxford University Press, 2021)
Providing an in-depth discussion of the promises and perils of specific types of theories of choice, this book shows how the selection of a specific theory of choice can make a difference for concrete legal questions, in particular in the regulation of the digital economy or in choosing between market, firm, or network.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 11, 2021).
Keywords: Social choice; Decision making; Sociological jurisprudence